Study of Social Media Marketing of A Local Snack Brand Toward Brand Authenticity and its Impact on Brand Preference - Sherly Theresia; Ferdi Antonio (International Journal of Economics Development Research (IJEDR), 2023)
Small and medium enterprises (SMEs) play an important role in national economic growth. Many SMEs in Indonesia produce packaged snacks, but not many of them use social media marketing effectively. This study aimed to examine the influence of the elements of social media marketing (SMM), which consist of attractiveness, trendiness, interaction, customization, information clarity on brand authenticity, and its impact on consumer preference, particularly on local snack brands produced by SMEs. The research model was modified from previous research and empirically tested with data from consumers of the local snack brand who viewed its Instagram social media in Indonesia. This research was carried out by a quantitative survey with cross-sectional data. Respondent data was taken purposively with a questionnaire instrument. A total of  210 respondents met the requirements and the data was analyzed through PLS-SEM. The results showed that the six antecedents of brand authenticity from social media marketing were found to have a significant and positive influence. Predominantly influence was found in trendiness and attractiveness content,  Brand authenticity demonstrated a significant direct impact on brand preference and mediated the SMM to brand preference. The findings of this study also show that brand authenticity can be adequately measured by its four dimensions, namely symbolism, continuity, integrity, and credibility. Further, this study encourages the local snack brands which are produced mostly by small and medium enterprises to pay attention to their branding, whereas SMEs can utilize brand authenticity as a differentiating tool.